Spectral X‐Ray Glitches in Monocrystalline Diamond Refractive Lenses. Issue 1 (21st August 2017) - Polikarpov, Maxim; Emerich, Hermann; Klimova, Nataliya; Snigireva, Irina; Savin, Valeriy; Snigirev, Anatoly
Abstract : X‐ray refractive lenses are widely used optical devices at today synchrotron X‐ray sources. In the present paper we demonstrate negative influence of the X‐ray diffraction on optical properties of monocrystalline X‐ray refractive lenses in operation. Several types of single‐crystal diamond lenses were studied in X‐ray spectroscopy mode at the European Synchrotron Radiation Facility. X‐rays were propagating through individual lenses, stacked together in a row, and the transmitted intensity was measured at different energies. While using the stack of crystallographically co‐aligned lenses, we obtained the strong maximal reduction of 35% in an intensity of the outgoing signal. The effect was caused by diffraction losses in the single‐crystal diamond and also called "X‐ray glitch." The magnitude of the effect was then minimized down to ∼10% by use of stacks with different crystallographic orientation of individual lenses inside. At the same time, X‐ray glitches did not affect any focal spot's size or shape while only arousing the darkening of the focal spot at exact energies of X‐ray glitches. Abstract : X‐ray refractive lenses are widely used optical devices at today's synchrotron X‐ray sources. Here Polikarpov et al. demonstrate a negative influence of X‐ray diffraction on the optical properties of monocrystalline lenses in operation. The effect arouses darkening of the focal spot while it does not affect any focal spot's size or shape.